Innovation in BCMA CAR-T therapy: Building beyond the Model T - Banerjee, Rahul; Lee, Sarah S.; Cowan, Andrew J. (Frontiers in Oncology, 2022)
Autologous chimeric antigen receptor T-cell (CAR-T) therapies targeting B-cell maturation antigen (BCMA) have revolutionized the field of multiple myeloma (MM) in the same way that the Ford Model T revolutionized the original CAR world a century ago. However, we are only beginning to understand how to improve the efficacy and usability of these cellular therapies. In this review, we explore three automotive analogies for innovation with BCMA CAR-T therapies in MM: stronger engines, better mileage, and hassle-free delivery. Firstly, we can build stronger engines in terms of BCMA targeting: improved antigen binding, tools to modulate antigen density, and armoring to reach the antigen itself. Secondly, we can improve “mileage” in terms of response durability through ex vivo CAR design and in vivo immune manipulation. Thirdly, we can implement hassle-free delivery through rapid manufacturing protocols and off-the-shelf products. Just as the Model T set a benchmark for car manufacturing over 100 years ago, idecabtagene vicleucel and ciltacabtagene autoleucel have now set the starting point for BCMA CAR-T therapy with their approvals. As with any emerging transformative technology, whether automotive or cellular, the best innovation and optimization is yet to come.